2020
DOI: 10.21203/rs.3.rs-33272/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fatal Central Nervous System Co-Infection with SARS-CoV-2 and Tuberculosis in a Healthy Child

Abstract: Background. Central and peripheral nervous system symptoms and complications are being increasingly recognized among individuals with pandemic SARS-CoV-2 infections, but actual detection of the virus or its RNA in the central nervous system has rarely been sought or demonstrated. Severe or fatal illnesses are attributed to SARS-CoV-2, generally without attempting to evaluate for alternative causes or co-pathogens.Case presentation. A five-year-old girl with fever and headache was diagnosed with acute SARS-CoV-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 23 publications
1
19
0
4
Order By: Relevance
“…Up to September 14, 2020, a total of 20 autopsy studies on neuropathology were retrieved, among which CNS detection of SARS‐CoV‐2 was negative in 12 (of 12) cases from three studies, 36,42,43 and positive in 58 (of 87) cases (66.7%) from nine studies, 46‐54 and unavailable for 109 cases in eight studies 35,37‐41,44,45 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to September 14, 2020, a total of 20 autopsy studies on neuropathology were retrieved, among which CNS detection of SARS‐CoV‐2 was negative in 12 (of 12) cases from three studies, 36,42,43 and positive in 58 (of 87) cases (66.7%) from nine studies, 46‐54 and unavailable for 109 cases in eight studies 35,37‐41,44,45 …”
Section: Resultsmentioning
confidence: 99%
“…On September 9, Freij et al 54 reported a 5‐year‐old girl who died from CNS co‐infection with SARS‐CoV‐2 and tuberculosis. Tests for SARS‐CoV‐2 RNA were negative in CSF, but positive in the biopsy tissue from the cerebellum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autopsy reports to date have described meningitis and/or encephalitis in small numbers of patients dying with COVID-19 disease 37–45 , and more frequently, both ischemic and/or hemorrhagic acute or subacute cerebrovascular lesions 37,39,44,4657 , but these have not always been supported by direct evidence of CNS SCV2 presence. Elements of the classical neuropathology of viral CNS infections 58,59 , including lymphocytic leptomeningitis and encephalitis, microglial nodules, perivascular lymphocytic cuffing, focal demyelination and viral inclusions, have most often been absent.…”
Section: Introductionmentioning
confidence: 99%
“…Elements of the classical neuropathology of viral CNS infections 58,59 , including lymphocytic leptomeningitis and encephalitis, microglial nodules, perivascular lymphocytic cuffing, focal demyelination and viral inclusions, have most often been absent. There have been at least 16 published studies 36,38,39,45,4750,6067 that used gold-standard RT-PCR methods to interrogate SCV2 genomic presence in postmortem brain tissue, but each of these have examined relatively few brain regions. The brain has hundreds of anatomically-distinct regions with possibly thousands of different cell phenotypes.…”
Section: Introductionmentioning
confidence: 99%